Child-Protection Systems – Slovenian Perspective - Burkelc Juras, Lina; Burkelc , Frida (Child-Protection Systems, 2025)
Abstract:This report describes the state of child protection system in Republic of Slovenia after the new Family Code entered into force in 2019. Children’s best interests can be protected by the following procedures: measures to protect the best interests of the child (in a strict sense), adoption and annulment of the adoption, granting parental responsibility to a relative, placing a child under guardianship, placing a child in foster care, deciding on the custody of a child, maintenance of a minor child (and of an adult child for as long as there is a maintenance obligation), the child’s contact with its parents and issues relating to the exercise of parental responsibility, which have a significant impact on the child’s development. The report also discusses the measures for protecting the best interests of children like urgent removal of a child, interim measures and measures of a more permanent nature (there are 6 of them and they are comprehensively regulated) in detail. It then highlights the unique Protocol of recommended practices for the execution of a decision on the removal of a child by direct extradition, which is a working tool prepared by a group of academics and experts from practice. Finally, we point out some interesting procedural aspects and accentuate some problems that arise in practice. Keywords: best interests of the child, interim injunction, measures of a more permanent nature, adoption, foster care, guardianship, granting parental responsibility to a relative